Marmota broweri Hall and Gilmore 1934 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Marmota broweri Hall and Gilmore, 1934. Can. Field Nat., 48:57. TYPE LOCALITY: U.S.A., Alaska, head of Kukpowruk River, "Point Lay.” DISTRIBUTION: Brooks Range of N. Alaska (U.S.A.) from near coast of Chukchi Sea to Alaska-Yukon border; perhaps also N. Yukon (Canada). COMMENT: Regarded by Hall and Kelson, 1959, and Hall, 1981, as a synonym of caligata, but Rausch and Rausch, 1971, Mammalia, 35:85- 101, and Hoffmann et al., 1979, Occas. Pap. Mus. Nat. Hist. Univ. Kans., 83:1 -56, considered broweri a distinct species. Type locality restricted by Rausch, 1953, Arctic, 6: 117. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 1), pp. 345-382 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 354, DOI: 10.5281/zenodo.7353023